2009
DOI: 10.1007/s00439-009-0728-4
|View full text |Cite
|
Sign up to set email alerts
|

The combined impact of metabolic gene polymorphisms on elite endurance athlete status and related phenotypes

Abstract: Endurance performance is a complex phenotype subject to the influence of both environmental and genetic factors. Although the last decade has seen a variety of specific genetic factors proposed, many in metabolic pathways, each is likely to make a limited contribution to an 'elite' phenotype: it seems more likely that such status depends on the simultaneous presence of multiple such variants. The aim of the study was to investigate individually and in combination the association of common metabolic gene polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 61 publications
(97 reference statements)
4
103
1
2
Order By: Relevance
“…There were no differences in the G894T allele frequencies in athletes stratified by the level of competitiveness (elite versus sub-elite) regardless of the athletes' status (power, "mixed" and endurance). Ahmetov et al [38] suggested that the difference in allelic frequencies between athletes within the same event category (for example strength/power sports), but with different levels of achievements may be explained by selection pressure. Specifically, the athletes possessing a "desired" allele or its combination are more likely to become elite.…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 99%
“…There were no differences in the G894T allele frequencies in athletes stratified by the level of competitiveness (elite versus sub-elite) regardless of the athletes' status (power, "mixed" and endurance). Ahmetov et al [38] suggested that the difference in allelic frequencies between athletes within the same event category (for example strength/power sports), but with different levels of achievements may be explained by selection pressure. Specifically, the athletes possessing a "desired" allele or its combination are more likely to become elite.…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 99%
“…Specifically, for men with high numbers (≥9) of endurance alleles (n = 26) compared with those with low numbers (≤8) of endurance alleles (n = 19), there was a greater number of slow-twitch fibers in the vastus lateralis (56.1% ± 1.8% vs. 43.8% ± 2.2%, p = 1.0 × 10 -4 ; these results remained statistically significant after correction for multiple testing) and a higher proportion of area occupied by those fibers (50.0% vs. 41.8%, p = .033; Ahmetov, Williams, et al, 2009).…”
Section: Combined Impact Of Gene Variants On Muscle-fiber Compositionmentioning
confidence: 89%
“…We recently found that the frequency of the VEGFR2 472Gln allele was significantly higher in endurance-oriented Russian athletes than in controls. The 472Gln allele was also shown to be significantly related to a higher proportion of Type I fibers of vastus lateralis (determined by immunohistochemistry) in both athletes (all-round speed skaters, n = 23, age 20.4 ± 0.5 years) and physically active men (n = 45, age 23.5 ± 0.4 years; Ahmetov, Hakimullina, et al 2009). …”
Section: Vascular Endothelial Growth-factor Receptormentioning
confidence: 96%
See 2 more Smart Citations